Adaptive DICOM images encryption using quadtree and lightweight ITUBee algorithm - Muntaha Abdulzahra Hatem; Balsam Abdulkadhim Hameedi; Jamal Nasir Hasoon; Fahad Ghalib Abdulkadhum (Universitas Ahmad Dahlan, 2025)
The encryption of medical images protects the privacy of patient information transmitted over networks and communications. In this paper, a lightweight encryption method for medical images is proposed, combining a quadtree-based segmentation and a modified ITUBee algorithm for encryption. A digital imaging and communications in medicine (DICOM) image is divided into variable-size blocks using the Quadtree technique, and the key is generated through a two-dimensional Henon map; the first dimension is used in the confusion process (bit permutation) of the pixel values, and the second sequence is used to generate the key schedule through the application round function. Different numbers of rounds are applied to the ITUBee method based on the size of the segments in the Quadtree, making the algorithm adaptive by increasing the round number when the block size is reduced. The method is used as a lightweight encryption method for encrypting all blocks, utilizing different round numbers for each block size to balance the degree of complexity with the total time consumption of the DICOM image. The result reinforces the proposed method, which produced a high mean squared error (MSE) between the DICOM image and the Encrypted One, and a lower peak signal-to-noise ratio (PSNR). The proposed generated numbers were also tested using national institute of standards and technology (NIST) to evaluate the randomness.